Autonomous Learning Strategies to Improve the Speaking Skills of the EFL University Students - Bao, Ivonia Reinalda Keri Dani; Aleksius, Madar; K. Danibao, Bernadus (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
This research is entitled "Autonomous Learning Strategies to Improve Speaking Skills of the Fifth Semester English Students of Widya Mandira Catholic University". The research questions were: 1) What are the types of Autonomous Learning Strategies used by the fifth-semester English students of Widya Mandira Catholic University to improve their speaking skills? 2) What are the most common mobile application forms used autonomously to improve the speaking skills of the fifth-semester English students of Widya Mandira Catholic University? 3) How are these strategies used as an effort to improve the speaking skills of the fifth-semester English students of Widya Mandira Catholic University? This study aims to find the types of autonomous learning strategies to improve speaking skills, the most common mobile application used to improve speaking, and to find out how the existing strategies are to improve the speaking skills of English students. This research employed a descriptive qualitative method. The instrument used in this research was an online questionnaire that involved a sample of 24 English students. The findings of this research were the type of learning strategy most often used by students was listening to English songs to improve their speaking skills and YouTube was the first application that students always used in independent learning and the students' efforts were to continue learning, making schedules, and setting goals and being consistent in the study.